2008
DOI: 10.1093/bja/aem347
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pulmonary vasoactive factors after sevoflurane anaesthesia in rats: a quantitative real-time polymerase chain reaction study

Abstract: Sevoflurane increased the expressions of ET-1, NOS3, and ADM. Our results suggest that the increased expressions of NOS3 and ADM may counteract that of ET-1 and so regulate pulmonary circulation under sevoflurane anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In our previous genomic studies, we administered 4.0% or 4.5% sevoflurane for 6 h and showed that sevoflurane anesthesia affected the expression of many genes and mRNAs in rat lungs (27,31). Here, the reason we experimented with both 2.0% and 4.0% sevoflurane is that inhalation of 4.0% sevoflurane affected circulation (Table 1), and as a result, hypotension, rather than the drug itself, could have affected miRNA expression.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In our previous genomic studies, we administered 4.0% or 4.5% sevoflurane for 6 h and showed that sevoflurane anesthesia affected the expression of many genes and mRNAs in rat lungs (27,31). Here, the reason we experimented with both 2.0% and 4.0% sevoflurane is that inhalation of 4.0% sevoflurane affected circulation (Table 1), and as a result, hypotension, rather than the drug itself, could have affected miRNA expression.…”
Section: Discussionmentioning
confidence: 92%
“…In our previous genomic studies, we showed that sevoflurane anesthesia affected the expression of many genes and mRNAs in rat lungs (27,31); therefore, we hypothesized that sevoflurane anesthesia also influences miRNA expression in the lung. Using TaqMan low-density arrays (TLDAs), we investigated sevoflurane-dependent changes in miRNA expression in rat lungs.…”
mentioning
confidence: 93%
“…The amplification of NPY and IL-1β was performed in a fast 96-well reaction plate (Applied Biosystems, Foster City, CA, USA), as previously described (25). Reactions were carried out in a 20-µl volume containing 10 µl of TaqMan Universal PCR master mix, 1 µl of TaqMan gene expression assays (Applied Biosystems), 8 µl of RNase-free water (Wako, Tokyo, Japan) and 20 ng of cDNA.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…A previous study found that HO-1 expression prevents rat livers from ischemia/reperfusion (I/R) injury when using anesthetic sevoflurane (Sevo) clinically (3). Inhalation of Sevo prior to ischemia increases the activity of HO-1 in the lung and protects from lung I/R injury in rats (4). I/R injury is an important model of oxidant-mediated ALI (5).…”
Section: Introductionmentioning
confidence: 99%